Insufficient Humidification of Respiratory Gases in Patients Who Are Undergoing Therapeutic Hypothermia at a Paediatric and Adult Intensive Care Unit. (20th April 2017) - Tanaka, Yukari; Iwata, Sachiko; Kinoshita, Masahiro; Tsuda, Kennosuke; Tanaka, Shoichiro; Hara, Naoko; Shindou, Ryota; Harada, Eimei; Kijima, Ryouji; Yamaga, Osamu; Ohkuma, Hitoe; Ushijima, Kazuo; et al.
Abstract : For cooled newborn infants, humidifier settings for normothermic condition provide excessive gas humidity because absolute humidity at saturation is temperature-dependent. To assess humidification of respiratory gases in patients who underwent moderate therapeutic hypothermia at a paediatric/adult intensive care unit, 6 patients were studied over 9 times. Three humidifier settings, 37-default (chamber-outlet, 37°C; Y-piece, 40°C), 33.5-theoretical (chamber-outlet, 33.5°C; Y-piece, 36.5°C), and 33.5-adjusted (optimised setting to achieve saturated vapour at 33.5°C using feedback from a thermohygrometer), were tested. Y-piece gas temperature/humidity and the incidence of high (>40.6 mg/L) and low (<32.9 mg/L) humidity relative to the target level (36.6 mg/L) were assessed. Y-piece gas humidity was 32.0 (26.8–37.3), 22.7 (16.9–28.6), and 36.9 (35.5–38.3) mg/L mean (95% confidence interval) for 37-default setting, 33.5-theoretical setting, and 33.5-adjusted setting, respectively. High humidity was observed in 1 patient with 37-default setting, whereas low humidity was seen in 5 patients with 37-default setting and 8 patients with 33.5-theoretical setting. With 33.5-adjusted setting, inadequate Y-piece humidity was not observed. Potential risks of the default humidifier setting for insufficient respiratory gas humidification were highlighted in patients cooled at a paediatric/adult intensive care unit. Y-piece gas conditions can be controlled to the theoretically optimal level by adjusting the setting guided by Y-piece gas temperature/humidity.